Two novel missense and frameshift mutations in exons 5 and 6 of the purine nucleoside phosphorylase (PNP) gene in a severe combined immunodeficiency (SCID) patient - Pannicke, Ulrich; Tuchschmid, Peter; Friedrich, Wilhelm; Bartram, Claus R.; Schwarz, Klaus (Human genetics, 1996)
Four percent of human severe combined immunodeficiency cases are caused by a deficiency of the enzyme purine nucleoside phosphorylase (PNP). In this study we investigated the molecular basis for this rare autosomal recessive disease. Sequence analyses led to the identification of two new mutations in the PNP gene: an A to G transition in exon 5, which leads to the substitution of tyrosine 192 by a cysteine residue, and a 1-bp deletion in exon 6, which causes premature translation termination of the PNP protein. Both PNP mutations affect predicted major structural motifs of the protein and result in posttranslational instability of the enzyme.